Gastric cancer: Environmental risk factors, treatment, and prevention - Woodman, Alexander; Akhtar, Mahmood; Al-Jamea, Lamiaa; Sagher, Malek; Sager, Mohamed (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Gastric cancer is a heterogeneous, multifactorial, aggressive disease that has been and remains one of the most common causes of cancer-related deaths and a significant public health issue worldwide. Currently, gastric cancer shows decreasing trends in its incidence and mortality in some geographic areas; however, the disease still shows a poor prognosis and remains difficult to cure. The prognosis for gastric cancer patients depends on the stage at which the gastric cancer is detected, and complete excision of the cancer is the only proven curative option. Gastric cancer prevention remains a priority. Patients at higher risk should be screened for early detection and chemoprophylaxis. Surgical resection enhanced by standardized lymphadenectomy remains the gold standard in the treatment of gastric cancer. Systemic therapy improves long-term disease-free survival compared to surgical treatment alone. Palliative chemotherapy in patients with inoperable gastric cancer prolongs survival and improves the quality of life. Demographic, ecological, environmental, cultural, and genetic variables all contribute to the heterogeneity of gastric cancer; however, environmental risk factors play an important role throughout all the stages of the disease progression, management, and surveillance. In this review, we address the role of important environmental risk factors in the onset of gastric cancer and highlight the current treatment modalities and prevention measures.
Keywords: Diet; gastric cancer; prevention; prognosis; risk factors; treatment